Mentoring as Two-Way Learning: An Australian First Nations/Non-indigenous Collaboration - Coff, Kathryn; Lampert, Jo (Frontiers in Education, 2019)
In this paper we explore how we are using the principles of two-way learning in a collaboration between two academics coming from different worldviews: an Australian First Nations scholar and a White, non-Indigenous scholar working together to promote First Nations Australian perspectives into the curriculum. This collaboration involves supporting each other, learning from each other, opening each other’s hearts and minds to each other’s worldviews. We act as each other’s mentors at different times, we are each other’s translators, have each other’s backs, and see each other as equals with different views to offer in order to create critical and sustainable change in all areas of education.